ISOLATION AND IDENTIFICATION OF PARTIAL GROWTH HORMONE (GH) mRNA OF TIGER SHOVELNOSE CATFISH Pseudoplatystoma fasciatum (LINNAEUS, 1766) - Erma Primanita Hayuningtyas; Eni Kusrini; Abinawanto Abinawanto (Indonesian Aquaculture Journal, 2022)
The growth of fish is regulated by growth hormones secreted in a limited amount by its pituitary glands. Tiger shovelnose catfish has a relatively faster growth indicating that some growth hormones suspectedly play roles in the process and could be used in improving other farmed fish species. This study aimed to isolate and identify the growth hormone (GH) mRNA gene in Tiger shovelnose catfish (Pseudoplatystoma fasciatum Linnaeus, 1766). The sample was isolated from the pituitary, the fish measuring 602 g and 43 cm body length; Total RNA was extracted using the Tri Reagent Kit, followed with cDNA synthesis. The success of the extraction was confirmed by quantification and PCR using the β-actin gene as an internal control. GH mRNA gene was isolated by RT-PCR method, with degenerated primers from seven catfish species sequence data in the NCBI gene bank. The single band from GH gene was cloned and sequenced. Total RNA quantification with a concentration of 227 ng/µL and purity of 1.821. The successful isolation of mRNA from the pituitary gland was confirmed by amplifying the β-actin gene generated at 300 bp. This isolation of the GH mRNA gene had a sequence length of 234 bp. Tiger shovelnose catfish GH gene consists of 17 amino acid residues. The GH gene of Tiger shovelnose catfish was close to that of striped catfish (P. hypophthalmus) and Indian catfish (Clarias batrachus) with almost similar homology value of 90.6 %. Partial GH gene from tiger shovelnose catfish can be used a molecular marker in revealing the role of growth hormone on fish development, fish biology, growth gene expression, selective breeding and other mechanisms related to the aquaculture.